Antiangiogenic virotherapy: VB-111 targeting glioma. (1st November 2016) - Khagi, Simon; Peters, Katherine B.
ABSTRACT: Introduction: High grade gliomas continue to represent a group of cancers that are difficult to control with current cytotoxics and antiangiogenics. With tumor angiogenesis representing a critical mechanism, there is an unmet need for novel types of treatment that can hone in on this important pathway of tumorigenesis. Areas covered: Virotherapy is a promising modality of cancer treatment that is defined by genetic manipulation of a virus to preferentially target neoplastic cells. VB-111 (ofranergene obadenovec) is a genetically modified adenovirus that is designed to selectively target tumor-associated endothelial cells. Utilizing PubMed and MEDLINE® databases, we identified key preclinical and clinical data pertaining to VB-111. We then reviewed ClinicalTrials.gov to determine the status of ongoing research. Expert opinion: Demonstrating safety and showing signs of efficacy in early phase clinical trials, VB-111 is being studied in combination with and without bevacizumab in a large phase 3 trial for recurrent glioblastoma. Given the data, VB-111 is a unique viral-mediated, antiangiogenic approach that has significant potential to make an impact in the field of oncology and neuro-oncology. We agree with the continued study of this agent in expanded and randomized cohorts to determine if VB-111 can indeed impact survival in glioblastoma.